2020
DOI: 10.21873/invivo.12107
|View full text |Cite
|
Sign up to set email alerts
|

Association Between M235T-AGT and I/D-ACE Polymorphisms and Carotid Atheromatosis in Hypertensive Patients: A Cross-Sectional Study

Abstract: Background/Aim: The renin-angiotensinaldosterone system (RAAS) may be implicated in carotid atheromatosis (CA) development. We aimed to assess the relationship of M235T-angiotensinogen (AGT) and insertion/deletion of angiotensin conversion enzyme (I/D-ACE) genotypes with CA in patients with essential hypertension (EHT). Patients and Methods: We determined the M235T-AGT and I/D-ACE genotypes, using PCR-RFLP methods, in 162 hypertensive subjects from three tertiary regional medical centers. The relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…DNA ladders, which are molecular weight markers, were electrophoresed along with the DNA fragments to estimate the sizes of fragments of interest, and 3 μl of 2% ethidium bromide was also used for staining. In 1X tris acetate EDTA (TAE) buffer, electrophoresis was performed, and a UV transilluminator was used to visualize the gel ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…DNA ladders, which are molecular weight markers, were electrophoresed along with the DNA fragments to estimate the sizes of fragments of interest, and 3 μl of 2% ethidium bromide was also used for staining. In 1X tris acetate EDTA (TAE) buffer, electrophoresis was performed, and a UV transilluminator was used to visualize the gel ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…[ 37 ] In Asian populations, the frequency of the TT genotype is 15% among the Japanese, [ 38 ] 14% among Koreans, and 0–3.7% among Indians. [ 6 , 7 , 19 21 , 37 , 38 ]…”
Section: Discussionmentioning
confidence: 99%
“…So far, most studies that tried to identify causative genes of stroke have focused on those involved in atherosclerosis, thrombosis, [12][13][14] homocysteine metabolism, [15][16][17][18][19] and hypertension. [17,[20][21][22] Large-scale studies have identified some genetic variants associated with ischemic stroke. The gene encoding for methylenetetrahydrofolate reductase, a key rate-limiting enzyme in the homocysteine metabolic pathway, is one of the most common susceptibility genes identified in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…The RAS not only plays a key role in the regulation of blood pressure in general (12,13,69), but it also plays a most significant role during gestation locally (3,4). As a crucial component of RAS, the ACE has a significant impact on the uteroplacental structure and function and is, therefore, of great importance for the deeper understanding of major pregnancy complications.…”
Section: Discussionmentioning
confidence: 99%